2019
DOI: 10.4012/dmj.2017-313
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of functionalized multi-walled carbon nanotubes on bone mesenchymal stem cell in rats

Abstract: Carbon nanotubes (CNTs) are promising biomaterials in the medical field, especially in tissue engineering of bone. However, the use of CNTs is largely confined by its unfavorable solubility and toxicity. To improve solubility and biocompatibility of CNTs, functionalization has been proven to be an effective strategy. Although various functionalized CNTs have been extensively studied, only few CNTs have the desired qualities. We compared the toxicity of several promising functionalized multi-walled carbon nanot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…For instance, Bottini et al [35] studied the toxicity of CNTs on human T cells and observed that CNTs could induce T lymphocyte apoptosis in a dose-dependent manner. However, Song et al [36] found that HA-MWCNTs have a favorable biocompatibility, with no obviously detrimental effects on bone marrow-derived stem cells. The CCK-8 assay was used to evaluate the proliferation of cells seeded on the scaffolds and in the control group in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Bottini et al [35] studied the toxicity of CNTs on human T cells and observed that CNTs could induce T lymphocyte apoptosis in a dose-dependent manner. However, Song et al [36] found that HA-MWCNTs have a favorable biocompatibility, with no obviously detrimental effects on bone marrow-derived stem cells. The CCK-8 assay was used to evaluate the proliferation of cells seeded on the scaffolds and in the control group in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of length, the longer CNTs were more likely to cause inflammatory responses and granulomatous formation in cells and tissues than the shorter CNTs. In diameter, the cytotoxicity of SWCNTs was stronger than that of MWCNTs, and MWCNTs with a small diameter had greater toxicity than those with larger diameter [120]. Some studies also indicated that controlling the size of MWCNTs can produce different toxic effects on human health, because their length and diameter play an important role in determining surface modifications that may affect vector transfection efficiency [121,122,123,124,125].…”
Section: Concerns and Current Solutions Of Cnts As Nanomaterials Fmentioning
confidence: 99%
“…The cytotoxicity of single-walled tubes was greater than that of multiwalled CNTs (MWCNTs), and toxic effects were higher for smaller MWCNTs than larger ones. Polyethylene glycol (PEG)–MWCNT composites exhibit biocompatibility on bone-marrow-derived stem cells of rats: PEG–MWCNT caused insignificant damage to DNA (the comet assay in Figure 2 b illustrates the circular shape evenly after electrophoresis) and the dead cell rate of stem cells was low ( Figure 2 c) [ 47 ].…”
Section: Cnts In Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
“…Adapted with permission from [ 17 ]; ( b ) live/dead cell assay of a polyethylene glycol–multiwalled CNT (PEG–MWCNT) composite (dead cells displayed in red); ( c ) the comet assay of PEG–MWCNT. Adapted with permission from [ 47 ].…”
Section: Cnts In Tissue Engineering and Regenerative Medicinementioning
confidence: 99%